A Colloidal‐Quantum‐Dot‐Based Self‐Charging System via the Near‐Infrared Band. Issue 25 (11th May 2018) - Baek, Se‐Woong; Cho, Jungmin; Kim, Joo‐Seong; Kim, Changjo; Na, Kwangmin; Lee, Sang‐Hoon; Jun, Sunhong; Song, Jung Hoon; Jeong, Sohee; Choi, Jang Wook; Lee, Jung‐Yong
Abstract: A novel self‐charging platform is proposed using colloidal‐quantum‐dot (CQD) photovoltaics (PVs) via the near‐infrared (NIR) band for low‐power electronics. Low‐bandgap CQDs can convert invisible NIR light sources to electrical energy more efficiently than wider spectra because of reduced thermalization loss. This energy‐conversion strategy via NIR photons ensures an enhanced photostability of the CQD devices. Furthermore, the NIR wireless charging system can be concealed using various colored and NIR‐transparent fabric or films, providing aesthetic freedom. Finally, an NIR‐driven wireless charging system is demonstrated for a wearable healthcare bracelet by integrating a CQD PVs receiver with a flexible lithium‐ion battery and entirely embedding them into a flexible strap, enabling permanent self‐charging without detachment. Abstract : A self‐charging platform via the near‐infrared band is proposed for low‐energy wearable electronics. A PbS‐based colloidal‐quantum‐dot photovoltaic is utilized as an energy receiver, showing higher efficiency and photostability under near‐infrared irradiation. The receiver, integrated with a flexible lithium‐ion battery, forms a self‐charging platform embedded into the strap of a healthcare bracelet, enabling user‐centric platforms to permanently self‐charge.